Short communication: A note on the new record of the amphibian fauna in Pulau Tinggi, Malaysia - Hui N.Y.; Md-Zain B.M.; Md-Zairi Z.; Abdul-Latiff M.A.B.; Ehwan Ngadi (Society for Indonesian Biodiversity, 2024)
Indexed by Scopus